2022
DOI: 10.3390/polym14163374
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigation of Gamma- and Neutron-Shielding Properties of Polysulfone (PSU) Polymer Material Using Geant4

Abstract: Polymers are widely used materials that have many medical and industrial applications. Some polymers have even been introduced as radiation-shielding materials; therefore, many studies are focusing on new polymers and their interactions with photons and neutrons. Research has focused on theoretical estimation of the shielding effectiveness of different materials. It is well known that theoretical studies on the shielding properties of different materials through modeling and simulation have many benefits, as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…) and the various levels of polypropylene sample thickness is depicted in Figure 3. The results show that gamma ray intensity decreases as shield thickness increases; this behavior is perfectly consistent with the equation's theoretical assumptions (1). In general, the findings broadly concur with those of earlier studies, [16].…”
supporting
confidence: 91%
See 1 more Smart Citation
“…) and the various levels of polypropylene sample thickness is depicted in Figure 3. The results show that gamma ray intensity decreases as shield thickness increases; this behavior is perfectly consistent with the equation's theoretical assumptions (1). In general, the findings broadly concur with those of earlier studies, [16].…”
supporting
confidence: 91%
“…It is common knowledge that materials with high atomic number elements (like Ba, Pb, and Bi) are used to attenuate gamma rays. Low atomic number materials, like polymers and plastics, are frequently used in medical applications as tissue equivalents and phantom materials [1][2][3][4][5][6]. In both primary and secondary defense against gamma radiation, polymers are crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Much of this research demonstrated that polymers' photon attenuation capabilities are promising, and their capacity to attenuate photons be boosted by combining them with various composites with high atomic numbers. Numerous investigated polymers also have high thermal neutron cross-sections and high neutron particle sensitivity, making them excellent neutron-shielding materials [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%